GIS "ETHNIC PROCESSES IN RUSSIA" - MANAGEMENT TOOL MULTINATIONAL TERRITORIES - V. S. Belozerov; A. N. Panin; A. A. Cherkasov (InterCarto. InterGIS, 2014)
The article discusses the possibility of using GIS technology in the study of ethnic processes in Russia. The researchers created GIS "Ethnic Atlas of Russia", which allows comprehensive GIS monitoring of ethnic processes in the country.